Comparative Analysis of the Novels "Dead Souls" by N.V.Gogol and "The Divine Comedy" by Dante Alighieri (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the comparative analysis of the novels Dead Souls by N.V. Gogol and The Divine Comedy by Dante Alighieri. The main goal is to study and identify the similarities and differences of the characters and plots in both works.